The Mythmakers - Weir, Keziah (New York : Marysue Rucci Books, 2023)
Sal Cannon's relationship is crumbling, and her career in journalism hits a low point after it's revealed that her profile of a playwright is full of inaccuracies. When she reads a short story by Martin Keller-- a much older author she met at a literary event years ago-- she discovers the story is about her and the moment they met. When Sal learns the story is excerpted from his unpublished novel, she reaches out to the story's editor, and learns that Martin is deceased. Desperate to leave her crumbling life behind and to read the manuscript from which the story was excerpted, Sal contacts Martin's widow, Moira. As she inserts herself into Moira's life, Sal sifts through Martin's papers. Who owns a story? And who is the one left to tell it? -- adapted from jacket.
new book 2024 winter.
Keywords: Women journalists -- Fiction; Ambition -- Fiction; Perspective (Philosophy) -- Fiction; Love -- Fiction; Manuscripts -- Fiction; Memory -- Fiction; Psychological fiction